Marine Pollution by State-Owned Companies in Offshore Areas Reviewed Based on the 1982 UNCLOS (Case Study: Oil Spill by PT Pertamina in Offshore Area of North Karawang) - Danial Danial; Belardo Prasetya Mega Jaya; Febi Sasti Rahayu (Faculty of Law, Universitas Jenderal Soedirman, 2023)
On July 12 2019, there was a pipe leak and a gas bubble oil spill belonging to PT Pertamina. PT Pertamina's pipeline leak in Karawang waters which has an impact from the oil spill threatens the ecosystem and the people around Karawang waters. Marine pollution cannot be seen only as a problem that occurs in the sea, because the oceans and land are an ecosystem unit that cannot be separated and are affected by one another. As a result of this incident, a problem arose regarding PT Pertamina's legal liability due to a pipe leak that caused marine pollution in Karawang waters. This research uses the normative juridical method. The purpose of this research is to find out the regulation of marine pollution actions carried out by PT Pertamina in the offshore area and to analyze the form of accountability. The results of the study can be concluded, firstly, that the regulation of marine pollution actions based on UNCLOS 1982 is contained in Articles 192, 194, 195, 196 and Law Number 32 of 2009 concerning Environmental Protection and Management. Secondly, in the form of liability for marine environmental pollution as a result of PT Pertamina's oil spill, there are three legal responsibilities (administrative liability, civil liability, and criminal liability).Keywords: Marine Pollution, Oil Spills, Accountability, UNCLOS 1982.